E-society - Shun Yung, Lee (2012)
Most of the university and colleges nowadays are using social networking service,which is an online platform that connects aspiring students with one another as well as with lecturers,professors,and staffs.The main purpose of social networking service is to focus on building and reflecting of social networks among people by sharing ideas,events, interests and activities within their individual networks. Some examples of popular social networking sites widely used today are Google+,Facebook,Twitter,MySpace,and Bibo. With the growing of Information and Communicate Technology ICT in Malaysia,academic portal in local Universities have enabled students not only to view personal academic information, but also to chat, share picture,upload or download files and post comments.It is being used by lecturers and students as a communication tool which is similar to a social networking site. With e-Society, students,teachers and professors of Faculty of Computer Systems and Sofware Engineering(FSKKP) in University Malaysia Pahang(UMP)are able to interact in group to extend their classroom discussion by posting comments,chatting live,uploading document files,photos and videos on this social networking site to assisting with homework outside of the classroom setting.E-Society also makes us possible to connect people who share interests and activities across education,economic,and geographic borders.Privacy of this system is concerned among its users by limiting users give out too much of personal information. Users of this system also need to be aware of unauthorized user from accessing their information.